Accuracy of Pelvic Ultrasound in Diagnosing Adnexal Torsion. (1st July 2019) - Ghulmiyyah, Labib; Nassar, Anwar; Sassine, Dib; Khoury, Sally; Nassif, Joseph; Ramadan, Hadi; Najem, Elie; Berjawi, Ghina
Abstract : Ovarian/adnexal torsion is a rather frequent occurrence in women of reproductive age group worldwide. Etiologies are quite diverse with ovarian lesions and corpus luteal cysts being the most two common. Pelvic or intravaginal ultrasound remains the first-line imaging modality used for diagnosis and evaluation of suspected ovarian/adnexal torsion. In this study, we have adopted a case-based statistical analysis to identify important sonographic markers and further evaluated their contribution in identifying ovarian torsion. Our study successfully determined the important sonographic markers. Our observation and analysis suggest that ovarian enlargement is the most sensitive marker. Ovarian edema was found to be the most specific marker to identify the ovarian torsion with higher level of accuracy and confidence. This pioneer study will provide valuable information and direction to the medical practitioners and radiologists for better diagnosis. Further studies with large sample size will help in establishing our findings universally.